Study of Star Formation Rate and Metallicity of an Interacting Dwarf Galaxy NGC 2604 - Chhatkuli, Daya Nidhi; Paudel, Sanjaya; Aryal, Binil (Journal of Institute of Science and Technology, 2020)
We present a study of the Sloan Digital all Sky Survey Data Release 12 (SDSS DR12) optical spectra of an interacting dwarf galaxy NGC 2604 that has redshift 0.0069. Thirteen characteristic emission lines were identified in the wavelength range of 3885 Å to 6742 Å, the strongest line was due to Hα emission with a value of emission-line flux 1538.8 erg/s/cm2/Å. The other twelve emission lines were observed because of OI doublet, Hβ, Hγ, Hδ, OIII doublet, HeI, SII doublet and NII doublet transitions. Eleven characteristic lines agreed perfectly with the Gaussian distribution with greater than 99.9 % coefficient of regression. However, full-width half maximum (FWHM) was found to be less than 5 Å. No absorption metallic lines were observed in the spectra which indicates that the galaxy was either newly formed. The line metallicity of the galaxy was found to be 8.4 dex and the extinction coefficient was 0.2134. The star formation rate due to Hα emission after extinction correction was found to be 0.0927 Mʘ year -1 which is almost double of the value (0.057 Mʘ year -1) before correction.